2017
DOI: 10.2337/db16-1036
|View full text |Cite
|
Sign up to set email alerts
|

α-1 Antitrypsin Enhances Islet Engraftment by Suppression of Instant Blood-Mediated Inflammatory Reaction

Abstract: Islet cell transplantation has limited effectiveness because of an instant blood-mediated inflammatory reaction (IBMIR) that occurs immediately after cell infusion and leads to dramatic β-cell death. In intraportal islet transplantation models using mouse and human islets, we demonstrated that α-1 antitrypsin (AAT; Prolastin-C), a serine protease inhibitor used for the treatment of AAT deficiency, inhibits IBMIR and cytokine-induced inflammation in islets. In mice, more diabetic recipients reached normoglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 44 publications
(76 reference statements)
2
61
0
Order By: Relevance
“…Furthermore, it is established that early inflammatory events accelerate detrimental host responses and fibrotic reactions, thus modulation of local inflammatory processes during early engraftment should lead to decreased adaptive responses. When compared to soluble anti‐inflammatory approaches, such as TNF‐α inhibitors, IL‐1 receptor antagonists, and anti‐tissue factor, the use of polymeric grafting is appealing, as this strategy imparts similar trends in positive islet engraftment but avoids the side effects associated with the systemic delivery of anti‐inflammatory agents …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is established that early inflammatory events accelerate detrimental host responses and fibrotic reactions, thus modulation of local inflammatory processes during early engraftment should lead to decreased adaptive responses. When compared to soluble anti‐inflammatory approaches, such as TNF‐α inhibitors, IL‐1 receptor antagonists, and anti‐tissue factor, the use of polymeric grafting is appealing, as this strategy imparts similar trends in positive islet engraftment but avoids the side effects associated with the systemic delivery of anti‐inflammatory agents …”
Section: Discussionmentioning
confidence: 99%
“…6 This innate response leads to substantial cell damage and loss during engraftment, with resulting stress signals and cellular debris potentiating adaptive immune response. The addition of systemic anti-inflammatory agents, such as TNF-α inhibitors (eg, etanercept and infliximab), IL-1 receptor antagonists (eg, anakinra), and others, improves islet engraftment and survival [11][12][13][14][15][16][17][18][19] ; however, increasing the drug regimen in CIT patients is not desirable.…”
mentioning
confidence: 99%
“…Many islets gathered for transplantation perish from ischemia and other biologic insults that may begin in the donor, increase during recovery of the pancreas, progress through purification and culture of the islets, then continue posttransplantation until a new blood supply develops 35, 36, 37, 38. Poor survival of donor islets has imperiled clinical deployment of islet transplantation because multiple donors are required to render a single recipient diabetes‐free.…”
Section: Effects Of Aat In Cell and Solid Organ Transplantationmentioning
confidence: 99%
“…Poor survival of donor islets has imperiled clinical deployment of islet transplantation because multiple donors are required to render a single recipient diabetes‐free. An “immediate blood‐mediated inflammatory reaction” upon reperfusion of islets is mediated at least in part by increased release of the pro‐coagulant “tissue factor” and activation of extracellular protease cascades, which can be inhibited by AAT 35, 37. The massive, clinically unacceptable loss of islets due first to cell death, then to inflammation and thrombosis in the peritransplant period sensitize the host and are exacerbated by the inability to achieve tolerance.…”
Section: Effects Of Aat In Cell and Solid Organ Transplantationmentioning
confidence: 99%
“…First, application of hAAT has been shown to alleviate symptoms in many disease models whereby immunity and inflammation were implicated, such as type 1 diabetes (Lu et al ., 2006; Zhang et al ., 2007; Ma et al ., 2010), islet cell transplantation (Lewis et al ., 2008), rheumatoid arthritis (Grimstein et al ., 2010, 2011), stroke (Moldthan et al ., 2014), and bone loss (Cao et al ., 2011). A recent study indicated AAT treatment inhibited instant blood‐mediated inflammatory reaction (IBMIR) and islet apoptosis after islet cell transplantation (Wang et al ., 2017). In addition, human AAT suppresses TNF and MMP‐12 production and enhances IL‐10 secretion in macrophages by increasing cAMP levels and activating cAMP‐dependent protein kinase A (Churg et al ., 2007; Janciauskiene et al ., 2007; Subramaniyam et al ., 2008).…”
Section: Introductionmentioning
confidence: 99%